Distance Learning : the Essential Guide. - Williams, Dr. Marcia L. (SAGE Publications, 1998)
TipsChapter 9 - Assessing Learning Outcomes; Guiding Principles; Methods of Assessment; Conclusion; Summary Tips; Chapter 10 - Program Evaluation; Evaluating Program Inputs; Program Processes; Assessing Outcomes; Analysis of Costs and Outcomes; Conclusion; Summary Tips; Chapter 11 - Accreditation; Guidelines for Distance Learning; Providing Evidence Regarding the Program's Effectiveness in Meeting the Guidelines; Conclusion; Summary Tips; Conclusion; Author Index; Subject Index; About the Authors.